Association between physiological serum total bilirubin concentrations and the progression of diabetic nephropathy - Zhang, Chenhui; Fang, Yuan; Lin, Zishan; Zhuo, Yongjie; Wan, Jianxin; Zhang, Xiaohong (Frontiers in Endocrinology, 2025)
PurposeTo analyze the relationship between physiological serum total bilirubin (STB) concentrations and the progression of diabetic nephropathy (DN).MethodsThe clinical features and pathological data of 159 patients with diabetic nephropathy confirmed by renal biopsy were retrospectively analyzed. They were divided into low bilirubin group (80 cases) and high bilirubin group (79 cases) according to the median of STB level. Clinical and pathological data of the two groups were collected and compared. The patients were followed up from the date of renal biopsy to June 30, 2024. Kaplan-Meier method and log-rank test was used to perform survival analysis. Univariate and multivariate Cox regression risk model were used to analyze the risk factors of diabetic nephropathy. A restricted cubic spline model was used to show the nonlinear association between STB and DN.ResultsWhen compared with physiologically high bilirubin group, patients in low bilirubin group might had higher level of serum creatinine, blood urea nitrogen, 24h urinary protein, urinary albumin to creatinine ratio (UACR), fibrinogen (Fib) and higher rate of K-W nodules, renal tubular atrophy, renal interstitial inflammation and lower level of eGFR, hemoglobin, PLT, suggesting that low bilirubin group had more severe indicators. Spearman correlation analysis showed that STB was positive associated with eGFR (r = 0.270, P < 0.001) while negative associated with serum BUN (r = -0.236, P = 0.003), serum creatinine(r=-0.256, P < 0.001), 24h urine protein(r = -0.257, P < 0.001), UACR (r = -0.287, P < 0.001) and Fib (r = -0.398, P < 0.001). The Kaplan Meier analysis revealed that high STB had a higher possibility of renal survival rate when compared with lower STB (P = 0.013). After univariate and multivariate Cox regression analysis, STB (HR = 0.445, P = 0.001), hemoglobin (HR = 0.983, P = 0.002), age (HR = 0.977,P = 0.033) and ACEI/ARB (HR = 0.340, P = 0.001) were independently protective factors for the DN progression, while serum creatinine (HR = 1.003, P =0.001), 24h urine protein (HR = 1.088, P = 0.005) and cholesterol (HR = 1.104, P = 0.002) were risk factors for DN progression. The restricted cubic spline model showed that there was a significant nonlinear association between DN progression and STB level when it was less than 6.085 µmol/LConclusionsOur findings suggest that STB may serve as a potential biomarker for the progression of diabetic nephropathy. Lower STB levels may help identify high-risk patients who could benefit from earlier or more intensive interventions to slow disease progression.